Energy-Biological Agricultural Complex - Guzyk, Dmytro; Borshch, Olena; Borshch, Volodymyr; Fediai, Bogdan (International Journal of Engineering and Technology, 2018)
When conducting modern farming on an industrial basis, there is a need to grapple with carbon dioxide surpluses in some premises, for example, it concerns livestock sheds- in order to improve the microclimate for raising productivity of animals, on the other hand there are production facilities that, according to  the  technology,  require artificial carbonation of their space, for example, in greenhouses  the process is used to increase the crop.The paper gives an overview of existing methods of supplying carbon dioxide to a greenhouse, which primarily provides  higher crops of plants when they are cultivated under glass. The air supply variant of gas saturated with carbon dioxide from the livestock shed  has been proposed.